Determinant Factors of National Entrepreneurial Activity: a Cross-Country Study - Widianto, Sunu (JDM (Jurnal Dinamika Manajemen), 2019)
The purpose of this study was to understand the phenomenon of entrepreneurship activity with a coherent paradigm that has not been widely explored. Entrepreneurship has been regarded as one of the important factor that support growth and socioeconomic development of a country because it can provides so many jobs, which ultimately will improve the welfare state and competitive advantage. Prior studies have been conducted research which is none of the comprehensive approach taken to explain the factors that encourage entrepreneurial activity that occurred in various countries around the world. This study found that Individualism negatively significant influence TEA which means the higher level of individualism of a country the lower Entrepeneurial activity. Moreover, cost enforcing contracts significantly influence national entrepreneurial activity which means the higher level of cost enforcing contracts the higher level of TEA.